Learning how to learn : how to succeed in school without spending all your time studying - Oakley, Barbara A., 1955-; Sejnowski, Terrence J. (Terrence Joseph); McConville, Alistair; Young, Oliver (New York, N.Y. : TarcherPerigee, 2018)
". . . in this new book for kids and teens, the authors reveal how to make the most of time spent studying. We all have the tools to learn what might not seem to come naturally to us at first--the secret is to understand how the brain works so we can unlock its power. This book explains: Why sometimes letting your mind wander is an important part of the learning process; How to avoid 'rut think' in order to think outside the box; Why having a poor memory can be a good thing; The value of metaphors in developing understanding; A simple, yet powerful, way to stop procrastinating . . ."--Provided by publisher.
Voice of Youth Advocates (V.O.Y.A.), August 2018
Includes bibliographical references and index.
Adult
Adult
Voice of Youth Advocates (V.O.Y.A.)
Keywords: Learning strategies -- Problems, exercises, etc; Study skills -- Study and teaching; Students -- Time management; Learning strategies -- Problems, exercises, etc; Study skills -- Study and teaching; Time management; JUVENILE NONFICTION / School & Education; JUVENILE NONFICTION / Study Aids / General; JUVENILE NONFICTION / Science & Nature / Biology